Elementary calcium release events from the sarcoplasmic reticulum in the heart - Brochet, Didier X.P. (2012)
Ca(2+) release events underlie global Ca(2+) signaling yet they are regulated by local, subcellular signaling features. Here we review the latest developments of different elementary Ca(2+) release features that include Ca(2+) sparks, Ca(2+) blinks (the corresponding depletion of Ca(2+) in the sarcoplasmic reticulum (SR) during a spark) and the recently identified small Ca(2+) release events called quarky SR Ca(2+) release (QCR). QCR events arise from the opening of only a few type 2 ryanodine receptors (RyR2s) - possibly only one. Recent reports suggest that QCR events can be commingled with Ca(2+) sparks and may thus explain some variations observed in Ca(2+) sparks. The Ca(2+) spark termination mechanism and the number of RyR2 channels activated during a Ca(2+) spark will be discussed with respect to both Ca(2+) sparks and QCR events.